Sexuality education for health professionals: A literature review - Vanessa Monteiro CESNIK; Thais ZERBINI (Estudos de Psicologia (Campinas))
Abstract The objective of this study was to review the scientific literature addressing educational actions related to the training of health professionals in sexuality between 2003 and 2013. The results obtained show that college seniors, recent college graduates, or those working in hospitals and other health care facilities are not adequately prepared to meet patients' needs regarding sexuality. Several studies have shown improvement in the health practitioners' ability to deal with patients' sexuality issues after participating in training programs in sexuality, regardless of the course load. According to the articles reviewed, in order to improve the performance and comfort level of health practitioners to deal with patients' sexuality concerns, investments in educational actions are necessary.